2007
DOI: 10.1007/s11434-007-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory effect of histamine on neuronal activity of rat cerebellar fastigial nucleus in vitro

Abstract: The cerebellar fastigial nucleus (FN) holds an important role in motor control and body balance. Previous studies have revealed that the nucleus is innervated by direct hypothalamocerebellar histaminergic fibers. However, the functional role of histaminergic projection in cerebellar FN has never been established. In this study, we investigated the effect of histamine on neuronal firing of cerebellar FN by using slice preparations. Sixty-five FN cells were recorded from 47 cerebellar slices, and a vast majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Actually, histamine actively participates in the regulation of many basic body functions, including the sleep‐waking cycle, energy and endocrine homeostasis, synaptic plasticity, learning, and motor control (Brown et al,2001; Haas and Panula,2003; Zhu et al,2006; Haas et al,2008). In the brain, neurons in several important subcortical motor structures, including the cerebellum (Li et al,1999; Tian et al,2000; Shen et al,2002; Tang et al,2007), basal ganglia (Korotkova et al,2002; Chen et al,2005; Zhou et al,2006), vestibular nuclei (Wang and Dutia,1995; Zhang et al,2008), and red nucleus (Chen et al,2003), are uniformly excited by histamine. Here we report that histamine not only excites spinal motoneurons but also potentiates their repetitive firing behavior via a parallel leftward shift of the f‐I relationship (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, histamine actively participates in the regulation of many basic body functions, including the sleep‐waking cycle, energy and endocrine homeostasis, synaptic plasticity, learning, and motor control (Brown et al,2001; Haas and Panula,2003; Zhu et al,2006; Haas et al,2008). In the brain, neurons in several important subcortical motor structures, including the cerebellum (Li et al,1999; Tian et al,2000; Shen et al,2002; Tang et al,2007), basal ganglia (Korotkova et al,2002; Chen et al,2005; Zhou et al,2006), vestibular nuclei (Wang and Dutia,1995; Zhang et al,2008), and red nucleus (Chen et al,2003), are uniformly excited by histamine. Here we report that histamine not only excites spinal motoneurons but also potentiates their repetitive firing behavior via a parallel leftward shift of the f‐I relationship (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that histamine may modulate neuronal activity in these motor structures and participate in motor control. Although a series of studies from our laboratory and other laboratories have already demonstrated an excitatory action of histamine on several subcortical motor structures, such as the cerebellum (Li et al,1999; Tian et al,2000; Shen et al,2002; Tang et al,2007), basal ganglia (Korotkova et al,2002; Chen et al,2005; Zhou et al,2006), vestibular nuclei (Wang and Dutia,1995; Zhang et al,2008), and red nucleus (Chen et al,2003), the effect of histamine on spinal motoneurons, the final common path for all signals from the central nervous system and the spinal intrinsic circuits to skeletal muscles, remains enigmatic.…”
mentioning
confidence: 97%